Wacana Stigmatisasi Perempuan Berpendidikan Tinggi yang Terefleksikan Melalui Media Sosial YouTube - Zulaikha, Siti; Firmonasari, Aprillia (MIMESIS, 2023)
Verbal stigmatization is part of the linguistic phenomenon. The effects of stigmatization can be felt in the near term and the future. However, stigmatization can negatively impact victims, so this phenomenon must be ended immediately. This study attempts to dissect the stigmatizing speech of highly educated women using Fairclough's AWK framework. The results of this study at the textual level found three types of speech: regulating, degrading, and cornering. The lingual form of stigmatization is found in the speech form ah, free, what, if, just, only, and only. In addition, it was also found that lingual expressions reflect stigmatization, namely in free speech “percuma dong” and “sayang banget”. The function of using the lingual form, based on the context of stigmatizing speech above, is to bring down mentally, influence negative thoughts, limit progress, and prohibit certain things. Furthermore, at the level of discursive practice from the five data above, there is an intertextuality between the discourse from the views of patriarchal and non-patriarchal societies. It shows that the stigmatization of highly educated women reflects patriarchal cultural thinking.